Hepatitis C Virus Clearance after Discontinuation of Pegylated Interferon Alpha-2a Monotherapy in a Child - Takeshi Endo; Koichi Ito; Tokio Sugiura; Kenji Goto (Case Reports in Medicine)
The present patient was a 4-year-old boy. His hepatitis C virus genotype was 2a, and his viral load was high (1400,000 U/mL). The pretreatment liver biopsy revealed no fibrosis or malignancy and mild chronic hepatitis; his Knodell's histological activity (HAI) score was 4. Single nucleotide polymorphism of IL28B (rs8099917) was major type. The patient began antiviral treatment with pegylated interferon alpha 2a (90 μg/week). At week 9, serum HCV RNA became undetectable, with a sensitivity of 50 copies/mL. Antiviral treatment was discontinued at week 11 because the ALT level increased to 610 U/L. After discontinuation of therapy, the patient’s serum HCV RNA status became positive again. The serum viral load increased to 100,000 U/mL. During this period, he had been observed without medication. Sixteen months after stopping treatment, serum HCV became undetectable. Over a 4-year period, HCV RNA became negative and his anti-HCV antibody titer gradually decreased. In conclusion, though antiviral therapy resulted in failure or incomplete therapy, a reduced viral load resulted in viral clearance in the present patient. Interleukin 28B genotype might have association with the clearance of hepatitis C virus after discontinuation of antiviral therapy.